A Note on "Economically Optimal Performance Evaluation and Control Systems": The Optimality of Two-Tailed Investigations - Young, Richard A. (Journal of Accounting Research, 1986)
Richard A. Young, A Note on "Economically Optimal Performance Evaluation and Control Systems": The Optimality of Two-Tailed Investigations, Journal of Accounting Research, Vol. 24, No. 1 (Spring, 1986), pp. 231-240